Hungry lightning : notes of a woman anthropologist in Venezuela - Yu, Pei-Lin, 1964- (University of New Mexico Press, 1997)
A young student of archaeology receives an offer she can't refuse, the chance to live among the Pume, a South American hunting-and-gathering people who call the tropical Venezuelan savannah home. During their time in the village of Doro Ana, the author and the principal researcher study a vanishing way of life in which cash money, the written word, automobiles, and airplanes are rare and frightening intrusions. Yu, adopted into a Pume family, provides an informal personal account of her two years' stay, describing the daily cycles of birth, growth, romance, sickness, healing, and death among the villagers. Yu's journal entries seek to present, through a young American's eyes, a sketch of her Pume family, their heroic struggle to survive in a changing world, and the power, humor, and mystery of the Pume way of life.